Sport Horses with Inflammatory Airway Disease (IAD) with Predominantly Eosinophils or Mast Cells Are More Predisposed to Poor Performance, Exercise Induced Pulmonary Haemorrhage (EIPH) and Have Shorter Careers When Compared to Horses with Neutrophilic IAD. (September 2014) - Boshuizen, B.; de Bruijn, C.M.; Dewulf, J.; Delesalle, C.J.
Abstract : Reasons for performing study: Clinical differences and variable response to therapy had been suspected between sport horses with predominantly eosinophils and/or mast cells in the bronchoalveolar lavage fluid (BALF) and horses with predominantly neutrophilia in the BALF. Objectives: To examine possible differences in performance, response to treatment and prognosis between both groups. Study design: Retrospective clinical study. Methods: A total of 174 client‐owned sport horses that were presented to the Wolvega Equine Clinic for respiratory problems between 2008 and 2013 were included. A questionnaire was used for follow‐up at least 3 months after diagnosis. Cytological BALF counts were considered increased when: neutrophils >5%; eosinophils >1% and mast cells >2%. Data were analysed using SPSS software and Chi square tests. Results: Cough and highest mucus scores were significantly more associated with neutrophilic IAD (P = 0.009 and P = 0.007). The neutrophilia group was also significantly more responsive to therapy, often including corticosteroid inhalation, and management optimisation (P = 0.001) and had better long‐term prognosis when compared to horses from the eosinophilic or mast cell groups (P<0.001). Lowest tracheal mucus scores were reported for the eosinophilic group, followed by the mast cell group. Haemosiderophage scores were significantly higher in the eosinophilic and mast cell groups (P<0.001). Poor performance was reported significantly more frequently in horses with eosinophils and mast cells as the main inflammatory cell population in their BALF (P = 0.001). Conclusions: Inflammatory airway disease with predominantly mast cells or eosinophils is associated with low endoscopic tracheal mucus scores. These horses are more predisposed to EIPH, poor performance and responded unfavourably to therapy when compared to horses with neutrophilic IAD. Ethical animal research:  Ethical committee oversight not currently required by this congress: retrospective study of clinical records. Explicit owner informed consent for participation in this study was not stated.Sources of funding:  Not stated.Competing interests:  None.